Analysis of Shi'a Da'wah in Karang Gayam and Blu'uran-Sampang Villages, Madura (Religious Moderation Study) - Nasution, Hasiolan; Hariyadi, Muhammad; Hude, Muhammad Darwis; Lubis, Muhamad Riyadi (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2025)
This article aimed to analyze Shi'a da'wah in Karang Gayam and Blu'uran-Sampang-Madura Villages using the theory of religious moderation from the Ministry of Religious Affairs of the Republic of Indonesia. This research was important because what is produced from Shi'a da'wah is one of the black records of religious life in Indonesia. The researcher used a qualitative method that is a case study, data was obtained through interviews, then analyzed thematically such as John W. Creswell's steps, while the validity of the data used triangulation of sources. The findings of this study revealed that there are several principles that were neglected in Shi'a da'wah in Karang Gayam and Blu'uran-Sampang Villages, Madura, namely ignoring the principles of justice and balance, the principles of amar makruf and nahi mungkar, the principle of comfort in religion and the principle of graduality. When this principle was disregarded, it is not surprising that da'wah efforts led to conflicts between Sunni communities that are rooted first and Shia groups as immigrant teachings. This research can be a reference material for da'wah practitioners in a multicultural society.